2011
DOI: 10.1108/01604951111127498
|View full text |Cite
|
Sign up to set email alerts
|

Serving the whole person: popular materials in academic libraries

Abstract: PurposeThis paper seeks to provide support and direction for academic libraries collecting popular materials.Design/methodology/approachThis paper offers a case study format supplemented by statistical and descriptive analyses.FindingsThe paper presents literature and case history‐based information on the debate surrounding popular materials collection in academic libraries. The case study provides concrete, cost‐effective steps for academic libraries to use in building popular materials collections.Practical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Institutions of higher education have started paying more attention to students’ well-being, not just education and professional development. The idea of educating the “whole person,” which is not unfamiliar to academic libraries either (Hallyburton et al, 2011), is quite tangible in the climate of contemporary academia and, more often than not, reflected in institutional mission statements or other established and written policies. Academic librarians could be greatly helped by the careful reading of these policies in their efforts to advocate for non-academic reading on campus.…”
Section: A Differentiated Approach To Readingmentioning
confidence: 99%
“…Institutions of higher education have started paying more attention to students’ well-being, not just education and professional development. The idea of educating the “whole person,” which is not unfamiliar to academic libraries either (Hallyburton et al, 2011), is quite tangible in the climate of contemporary academia and, more often than not, reflected in institutional mission statements or other established and written policies. Academic librarians could be greatly helped by the careful reading of these policies in their efforts to advocate for non-academic reading on campus.…”
Section: A Differentiated Approach To Readingmentioning
confidence: 99%
“…Thirty-one titles had holds placed at several of the different institutions. These titles appeared to be either textbooks or New York Times Bestseller books (Hallyburton, Buchanan, & Carstens, 2011). Of the 11 institutions evaluated, most had a drop in the number of multiple holds submitted over the past three academic years.…”
Section: Holds/recallsmentioning
confidence: 99%
“…It is frequently suggested that students who are seeking leisure reading can instead be directed to a public library (Dewan, 2010;Diers & Simpson, 2012;Elliott, 2007;Rathe & Blankenship, 2006). Despite these observations, there is ample evidence to support the provision of a leisure reading collection within an academic library (Bosman, Glover & Prince, 2008;Dewan, 2010;Elliott, 2007;Fleet, 2003;Gilbert & Fister, 2011;Hallyburton, Buchanan & Carstens, 2011;Hsieh & Runner, 2005;Rathe & Blankenship, 2006).…”
Section: Introductionmentioning
confidence: 99%